Internal hiring or external recruitment? - Jed DeVaro (IZA World of Labor, 2016)
Hiring is one of a firm's most important decisions. When an employer fills a vacancy with one of its own workers (through promotion or lateral transfer), it forgoes the opportunity to fill the position with a new hire from outside the firm. Although both internal and external hiring methods are used, firms frequently have a bias favoring insiders. Internal and external hires differ in observable characteristics (such as skill levels), as do the employers making each type of hiring decision. Understanding those differences helps employers design and manage hiring policies that are appropriate for their organizations.
Keywords: M51; 330; internal promotion; external recruitment; lateral transfers; hiring